INVOLVEMENT OF NON-PROFESSIONALS IN CATALOGUING: A SURVEY OF PRACTICES IN THREE ACADEMIC LIBRARIES IN NIGERIA - Yusuf, Felicia; Nkiko, Christopher (Malaysian Journal of Library and Information Science, 2010)
The study examined the involvement of non-professionals in cataloguing practices in three academic libraries in Nigeria. Twenty five respondents comprising current cataloguers and those who had worked as cataloguers were used for the study. A descriptive survey method using a self-constructed questionnaire was used. Four research questions were posed and analysed using frequency counts and percentages. Results showed that the involvement of non-professionals in cataloguing is fast becoming a reality, with one university library depending more on non-professionals while the other two showed less dependence on them. Methods adopted by these libraries to ensure quality control include close supervision by professionals, training non-professionals in copy cataloguing, and designation of a librarian to constantly edit the catalogue for possible re-cataloguing. The use of prepared worksheets by librarians to be keyed in by non-professionals is the least used strategy. Other major findings include changes in cataloguing practices which comprise online cataloguing, cataloguing of Internet resources and electronic files, copy-cataloguing, different metadata structures, introduction of OPAC and the involvement of non-professionals in cataloguing practices. Outsourcing, procurement of ICT, employment of Systems Engineers as part of library staff, attendance of workshops and conferences among others were some of the strategies adopted to cope with these changes; however, the application of ICT was the most frequently used strategy. The study concluded that cataloguing practices in the libraries sampled have witnessed changes as a result of the application of ICT in organizing library materials which has in turn changed the role of cataloguers from merely providing bibliographic details of materials to that of supervision and other administrative functions, and in order to maintain relevance, librarians have been forced to build capacity in the area of ICT.